Analisis Sentimen Aplikasi Identitas Kependudukan Digital (IKD) Menggunakan Metode Naïve Bayes - Rahmat Hidayat; Rohim Nur Rahman; Muhammad Reifin Perdana; Arbansyah Arbansyah (International Forum of Researchers and Lecturers, 2024)
Digital Population Identity (IKD) is a digital-based location data innovation through a mobile application with a photo or QR Code. The government's objective is to reduce the physical prints of KTP as well as the use of blank KTP-el in the hope of administrative efficiency. ICT is integrated with health services, education, banking, and taxation, facilitating public access in the era of technological development. However, in remote areas, limited internet access and minimal socialization raise concerns about the security of digital identity data being considered. Social media, especially YouTube, is a channel platform used by the public to convey opinions, opinions and comments about ICTs. So that's why sentimental analysis is needed using the Naive Bayes algorithm to help understand public opinion. The tests were conducted using Orange on 1,561 data showing accuracy, precision, recall, and F1 above 90%. The results of this analysis can serve as a guide for staff in interacting with the community for the implementation of Digital KTP through IKD, as well as improving services regarding the applications provided.